Highly sensitive multiplex protein detection by droplet‐free digital ELISA. Issue 2 (4th December 2018) - Akama, Kenji; Shirai, Kentaro; Suzuki, Seigo
Abstract: Digital enzyme‐linked immunosorbent assay (ELISA) is a single molecule counting technology and is one of the most sensitive immunoassay methods. The key aspect of this technology is to concentrate enzyme reaction products from a single target molecule in femtoliter droplets. On the other hand, we have developed a novel Digital ELISA that does not require droplets; instead, enzyme reaction products are concentrated using a tyramide signal amplification system. In this study, we present a method that enables the multiplex detection of proteins based on Droplet‐free Digital ELISA. First, two types of paramagnetic beads immobilized with antibodies specific to different target proteins were incubated with a sample solution, and target proteins were captured on their specific beads. Then, these beads were labeled with horseradish peroxidase (HRP), and tyramide substrate reacted with HRP on beads, resulting in products of this reaction deposited on those beads. This signal amplification on beads makes it possible to count the number of labeled beads digitally. We used this approach to simultaneously detect IL‐6 and HBs Ag with single molecule resolution. The obtained limit of detections were 0.1 pg/mL and 0.013 IU/mL, respectively. Our method has potential applications in simple in vitro diagnostic systems for simultaneous and high‐sensitive detection of protein biomarkers.